Optical effects of polar stratospheric clouds on the retrieval of TOMS total ozone - Torres, O.; Ahmad, Z.; Herman, J. R. (1992)
Small areas of sharply reduced ozone density appear frequently in the maps produced from polar region total ozone mapping spectrometer (TOMS) data. These mini-holes are of the order of 1000 km in extent with a lifetime of a few days. On the basis of measurements from ground-based instruments, balloon-borne ozonesondes, and simultaneous measurements of aerosol and ozone concentrations during aircraft flights in the Arctic and Antarctic regions, the appearance of polar stratospheric clouds (PSCs) are frequently associated with false reductions in ozone derived from the TOMS albedo data. By combining radiative transfer calculations with the observed PSC and ozone data, it is shown that PSCs located near or above the ozone density maximum (with optical thickness greater than 0.1) can explain most of the differences between TOMS ozone data and ground or in situ ozone measurements. Several examples of real and false TOMS mini-hole phenomenon are investigated using data from the 1989 Airborne Arctic Stratospheric Expedition (AASE) and from balloon flights over Norway and Sweden.